Longitudinal follow‐up of patients with thalassaemia intermedia who started transfusion therapy in adulthood: a cohort study. (19th May 2020) - Ricchi, Paolo; Meloni, Antonella; Pistoia, Laura; Spasiano, Anna; Rita Gamberini, Maria; Maggio, Aurelio; Gerardi, Calogera; Messina, Giuseppe; Campisi, Saveria; Allò, Massimo; Renne, Stefania; Righi, Riccardo; et al.
Summary: We longitudinally evaluated the effects of regular blood transfusions (BTs), in the real‐life context of the Myocardial Iron Overload in Thalassaemia network, in patients with thalassaemia intermedia (TI). We considered 88 patients with TI (52 females) who started regular BTs after the age of 18 years. Magnetic resonance imaging was used to quantify iron overload and biventricular function. For 56·8% of the patients there were more than two indications for the transition to regular BTs, with anaemia present in 94·0% of the cases. A significant decrease in nucleated red blood cells, platelets, lactate dehydrogenase, bilirubin, and uric acid levels was detected 6 months after starting regular BTs. After the transition to the regular BT regimen there was a significant increase only in the frequency of hypothyroidism and osteopenia, and a significant decrease in liver iron and cardiac index. The percentage of chelated patients increased significantly after starting regular BTs. The decision to regularly transfuse patients with TI may represent a way to prevent or slow down the natural progression of the disease, despite the more complex initial management.